Plant extracts controlling the citrus mealybug, Planococcus citri (RISSO, 1813) (Hemiptera: pseudococcidae) in coffee plants - Santa-Cecília, Lenira Viana Costa; Santa-Cecília, Flávia Viana; Pedroso, Elizabeth do Carmo; de Sousa, Marcella Viana; Abreu, Fernanda Aparecida; Oliveira, Denilson Ferreira; Carvalho, Geraldo Andrade (Coffee Science - ISSN 1984-3909, 2011)
The citrus mealybug, Planococcus citri (Risso, 1813), is a sap-sucking insect that attacks the rosettes of coffee plants, causing losses to production. A potential strategy to be adopted in the integrated management of this pest (IPM) comprises the use of plant extracts with insecticidal activity. Thus, to determine the potential of some plants in the control of P. citri, the activities of extracts prepared from 188 different species of plants collected in the southern state of Minas Gerais were evaluated under laboratory conditions. Those extracts that caused the highest mortality of nymphs were selected to conduct more detailed tests to investigate methods of application of the extracts, different plant parts of selected plants and different extract concentrations. Among the 234 extracts studied, only those from Persea Americana Mill. were selected, since they caused the greatest mortality of mealybug nymphs. The most efficient extract was prepared from the husk (coconut shell) of avocado, at 250mg/mL in water. When applied with an atomizer, such extract caused 77.0% mortality of P. citri nymphs.